If love is blind, then hate cannot see: hate within enduring parenting disputes. Issue 3 (3rd July 2019) - Francia, Leanne; Millear, Prudence; Sharman, Rachael
Abstract: Drawing on interviews with separated mothers ( N = 36) this Australian qualitative study explored "hate" in a child custody context within enduring parenting disputes. This preliminary study observed that hate may be present within enduring parenting disputes. A conceptualization of hate, being circular theory of hate in co-parental conflict was developed which tentatively proposes that in a post separation context, hate may functionally serve as a self-protective mechanism that enables a parent to avoid experiencing their own emotions; avoid confronting or taking responsibility for their own behavior; or avoid facing their own lived experiences. Three themes emerged from the study that may contribute to understanding hate's genesis, growth, and stability post separation. Firstly, an inability or unwillingness to self-reflect, secondly, inverse caring, and thirdly, relentlessness. Practitioners working with hate in a child custody context may consider these tentative observations when identifying barriers parents might experience that prevent them from keeping their child's needs front and center following separation.